Investigation of cobalt sulfate precipitation by alcohol and influencing factors - (:unkn) unknown (SOC MINING METALLURGY EXPLORATION INC, 2013)
This work presents a method for the precipitation of cobalt sulfate by alcohols, specifically ethanol and methanol. The effect of the initial concentration of cobalt, the volumetric ratio of alcohol to cobalt sulfate solution, the addition of sulfuric acid and ammonia, and the effects of common ions on the precipitation percentage were investigated. The performances of ethanol and methanol were compared in terms of the precipitation percentage of cobalt sulfate, and explanations for different performances are offered. In the sulfate-based solution, the alcohol was shown to displace water ligands from the first coordination sphere of the cobalt(II) cations, which led to the precipitation of the cobalt ions as cobalt sulfate heptahydrate. SEM analysis revealed that the particle sizes of the powders produced by this method are smaller than those of commercially available cobalt sulfate. The scientific literature contains no data on the solubility of cobalt sulfate in ethanol. In this study, the solubility product constant (K-sp) for cobalt sulfate was experimentally calculated to be approximately 1.15 x 10(-5).
Keywords: Sulfate precipitation method; Cobalt; Ethanol; Methanol; Solubility product constant